2016
DOI: 10.1098/rsif.2015.0984
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap: wound healing in insects restores mechanical strength by targeted cuticle deposition

Abstract: If an insect is injured, can it repair its skeleton in a manner which is mechanically strong and viable? Previous work has described the biological processes that occur during repair of insect cuticle, but until now, there has been no biomechanical assessment of the repaired area. We analysed the biomechanics of the injury repair process in the desert locust (Schistocerca gregaria). We show that after an incision, a healing process occurred which almost doubled the mechanical strength of locust tibial cuticle,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…This is then sclerotized (or tanned) over the next 12 he3 days (Andersen et al, 1996;Hepburn and Joffe, 1974;Chapman, 2013). In experiments conducted after this tanning process was complete, it has been shown (Parle et al, 2016b) that in the first 21 days post moult, the insect deposits cuticle quite rapidly, slowing down after this time period. This rapid deposition undoubtedly serves to reinforce the leg which would be prone to buckling failures early on while still relatively slender (Parle et al, 2016c).…”
Section: Modelling Of the Cuticlementioning
confidence: 96%
See 2 more Smart Citations
“…This is then sclerotized (or tanned) over the next 12 he3 days (Andersen et al, 1996;Hepburn and Joffe, 1974;Chapman, 2013). In experiments conducted after this tanning process was complete, it has been shown (Parle et al, 2016b) that in the first 21 days post moult, the insect deposits cuticle quite rapidly, slowing down after this time period. This rapid deposition undoubtedly serves to reinforce the leg which would be prone to buckling failures early on while still relatively slender (Parle et al, 2016c).…”
Section: Modelling Of the Cuticlementioning
confidence: 96%
“…Much research has been done into the roles played by chemistry (Lai-Fook, 1968;Rowley and Ratcliffe, 1978;Wright, 1987), biology (Wigglesworth, 1937;Locke, 1966;Marmaras et al, 1996;Dillaman and Roer, 1980;Lai et al, 2001) and genetics (Galko and Krasnow, 2004;Belacortu and Paricio, 2011) involved during the wound healing of insects, but how effective are these processes at restoring the original preinjury properties such as strength, stiffness and toughness e crucial for the survival of a limb and the fitness of the insect e to the cuticle? One such study (Parle et al, 2016b) showed that the deposition of a patch of new cuticle underneath a wound is crucial, and can restore the strength of an injured leg to 66% of its original strength. The patch (coloured in green in Fig.…”
Section: Major Damagementioning
confidence: 99%
See 1 more Smart Citation
“…This new material can be seen to have fractured during the bending test. It was found that the repair process increased the strength of the damaged leg by about a factor of two, bringing it to about 66% of the strength of the original, intact leg . The repair seems to rely mainly on the effect of the patch material to reduce the stress concentration effect of the cut, although it is also possible that the properties of the material itself may change.…”
Section: Self‐repair In Endoskeletons and Exoskeletonsmentioning
confidence: 99%
“…This phenomenon has, until now, not been investigated for any other biological material. In our previous work on insect cuticle, we showed that desert locusts are capable of repairing macroscopic damage (O'Neill, DeLandro, & Taylor, , Parle, Dirks, & Taylor, ). We applied scalpel cuts and puncture wounds to the hind tibia, sufficiently large to induce significant loss of strength, and found that repair occurred in the form of targeted cuticle deposition.…”
Section: Introductionmentioning
confidence: 99%